Android Security Cookbook - Keith Makan, Scott Alexander-Bown (Packt Publishing, 2013)
Android Security Cookbook' breaks down and enumerates the processes used to exploit and remediate Android app security vulnerabilities in the form of detailed recipes and walkthroughs."Android Security Cookbook" is aimed at anyone who is curious about Android app security and wants to be able to take the necessary practical measures to protect themselves; this means that Android application developers, security researchers and analysts, penetration testers, and generally any CIO, CTO, or IT managers facing the impeding onslaught of mobile devices in the business environment will benefit from reading this book.